Access to a stabilized i-motif DNA structure through four successive ligation reactions on a cyclopeptide scaffold. Issue 32 (5th August 2020) - Devaux, Alexandre; Bonnat, Laureen; Lavergne, Thomas; Defrancq, Eric
Abstract : Four successive chemical ligations were used for the assembly of a sophisticated biomolecular system allowing the formation of a stabilized i -motif DNA at pH 7. Abstract : i -Motifs are largely underexplored tetraplex nucleic acid structures which have been suggested to perform essential biological functions and might constitute future therapeutic targets. i -Motifs generally require acidic conditions to fold in vitro, a particularity which significantly complicates the use of native i -motif forming sequences for interaction studies with potential ligands and biological components ( e.g. proteins). In this context, we report herein on the assembly of a peptide–DNA conjugate capable of folding at room temperature into a stable i -motif structure at neutral pH. To achieve the controlled assembly of the i -motif forming conjugate, we developed a new synthetic pathway of four successive orthogonal ligation reactions between bifunctional C-rich DNA strands and a tetrafunctional cyclopeptide scaffold.